Effects of dabigatran according to age in atrial fibrillation. Issue 13 (17th February 2017) - Lauw, Mandy N; Eikelboom, John W; Coppens, Michiel; Wallentin, Lars; Yusuf, Salim; Ezekowitz, Michael; Oldgren, Jonas; Nakamya, Juliet; Wang, Jia; Connolly, Stuart J
Abstract : Objective: The prevalence of atrial fibrillation (AF) and the risk of stroke and bleeding vary according to age. To estimate effects of dabigatran, compared with warfarin, on stroke, bleeding and mortality in patients with AF in the Randomized Evaluation of Long-Term Anticoagulant Therapy (RE-LY) trial according to age, we analysed treatment effects using age as a continuous variable and using age categories. Methods: RE-LY included 10 855 (59.9%) patients aged <75 years, 4231 patients (23.4%) aged 75–79 years, 2305 (12.7%) aged 80–84 years and 722 (4.0%) aged ≥85 years at baseline. Results: Benefits of dabigatran versus warfarin regarding stroke (HR range 0.63 (95% CI 0.46 to 0.86) to 0.70 (0.31 to 1.57) for dabigatran 150 mg twice daily), HR range 0.52 (0.21 to 1.29) to 1.08 (0.73 to 1.60) for dabigatran 110 mg twice daily) and intracranial bleeding were maintained across all age groups (interaction p values all not significant). There was a highly significant interaction (p value interaction <0.001) between age and treatment for extracranial major bleeding, with lower rates with both doses of dabigatran compared with warfarin in younger patients (HR 0.78 (0.62 to 0.97) for 150 mg twice daily, HR 0.72 (0.57 to 0.90) for 110 mg twice daily) but similar (HR 1.50 (1.03 to 2.18) for 110 mg twice daily) or higher rates (HR 1.68 (1.18 to 2.41) for 150 mg twice daily) in older patients (≥80 years). Conclusion: Effects of dabigatran compared with warfarin on stroke prevention and intracranial bleeding are consistent across all age groups. Effects of dabigatran on extracranial major bleeding are age dependent, supporting selection of dabigatran 110 mg twice daily for elderly patients (age ≥80 years). Trial registration number: Clinical trial registration number: https://clinicaltrials.gov NCT00262600 .